Vesicular-Arbuscular Mycorrhizae in Tree - Legumes and its Rhizospheric Soils in Alagar Hills - Santhaguru, K.; Gladis Ponmalar, S. B.; Karunakaran, R. (Indian Forester, 1995)
The occurrence of Vesicular-Arbuscular Mycorrhizal (VAM) spores in the rhizospheric soils of tree-legumes and a liane of Alagar Hills and the extent of infection in the roots of these legumes were investigated. Among the species investigated, 75% of them showed VAM infection, but with varying frequency. Altogether 21 species of VAM fungi belonging to six genera viz. Acaulospora, Entrophospora, Gigaspora, Glomus, Sclerocystis and Scuteilospora were recorded.